Treatment outcome and its predictors among children with epilepsy on chronic follow-up in Ethiopia: a systematic review and meta-analysis - Gebremariam Wulie Geremew; Yilkal Abebaw Wassie; Gebresilassie Tadesse; Setegn Fentahun; Abebaw Setegn Yazie; Sisay Sitotaw Anberbr; Gebremariam Genet; Abaynesh Fentahun Bekalu; Gashaw Sisay Chanie; Tekletsadik Tekleslassie Alemayehu (BMC, 2024)
Abstract Background Seventy percent of epileptic patients may not experience seizures if they receive proper treatment with antiepileptic drugs (AEDs). However, many children and adolescents face poor seizure control (PSC). Therefore, the purpose of this review is to systematically and quantitatively summarize the pooled prevalence of PSC and its predictors among children with epilepsy in Ethiopia. Methods The following databases were used to conduct a thorough literature search: Africa Journal of the Online Library, Hinari, Google Scholar, PubMed, Science Direct, EMBASE, Cochrane Database, Sci-Hub, and Scopus. To evaluate the quality of the studies, Newcastle‒Ottawa Scale (NOS) checklists were utilized. The data on study characteristics and prevalence estimates were then combined via random effects meta-analysis, followed by subgroup and sensitivity analyses. Both visual and statistical analyses were employed to assess for any potential publication bias. Results This review analyzed a total of 12 main studies and reported that the overall prevalence of PSC was 42.42% (95% CI: 33.42-51.42). However, there was significant heterogeneity in the results based on the study region, design, and seizure-free period. The subgroup analysis revealed that the highest prevalence of PSC was found in Southern Nations, Nationalities, and Peoples' (SNNPs) studies (61.88%; 95% CI: 35.91-87.85), studies with a cross-sectional design (46.73%; 95% CI: 36.83-56.62), and studies with a seizure-free period < 6 months (44.69%; 95% CI: 34.51-54.86). However, the lowest prevalence was observed in the Amhara region (35.54%; 95% CI: 27.40-43.67), cohort studies (29.53%; 95% CI: 21.26-38.21), and studies with a seizure-free duration of six months or more (41.64%; 95% CI: 29.94-53.35). The results also revealed a significant correlation between PSC and medication nonadherence (4.64, 95% CI: 2.84-7.58), comorbidities (2.08, 95% CI: 1.01-4.26), and seizure type (3.59, 95% CI: 1.18-10.8). Conclusion Based on this review, the findings suggest a notable prevalence of poorly controlled seizures (PSC) among children with epilepsy who are receiving antiepileptic drugs (AEDs) in Ethiopian outpatient epilepsy clinics. Seizures of tonic‒clonic status, comorbidities, and medication nonadherence were associated with poor seizure control.